ROLE OF VITAMIN E (α TOCOPHEROL) TO PREVENT THE SPERMATOGONIA, SERTOLI CELL, AND LEYDIG CELL DAMAGE IN RATS TESTICLE (STRAIN WISTAR) AFTER CISPLATIN TREATMENT - Krismantoro, Rahmad; Rizaldi, Fikri; Soebadi, Doddy M (Indonesian Urological Association, 2019)
Objective: To determine the difference in spermatogonium cells, leydig cells and sertoli cells count in white rats testicle (wistar strains) obtained with the combination of cisplatin and vitamin E compared with that only received cisplatin. Material & Methods: There were 4 random groups out of a total of twenty four winstar strain rats (n=6). The control group (I) injected normal saline 0.9% intraperitoneally (i.p.) as the placebo on the 3rd week. Group (II) given cisplatin (5 mg/kgbw) injection i.p. on 3rd week, Group (III) given cisplatin injection 5 mg/kgbw i.p. on 3rd week + vitamin E 50 mg/kgbw by gavage for 7 weeks and group (IV) cisplatin injection 5mg/kgbw i.p. on 3rd week + vitamin E 200 mg/kgbw by gavage for 7 weeks. Vitamin E was given 3 weeks before up to 4 weeks after cisplatin injection (total 7 weeks). Observations by calculating the average number of spermatogonia, sertoli and leydig cells on a cross-sectional section of the seminiferous tubule with Haematoxylin-Eosin staining using a 400x light magnification microscope. Results: Cisplatin decreases spermatogonia, sertoli, and leydig cells significantly against control. Vitamin E 200 mg/kgbw significantly increased the number of spermatogonium, sertoli, and leydig cells (p<0.05) compared to group in combination with vitamin E 50 mg/kg bw and cisplatin or cisplatin only group. Only leydig cells count was significantly increased in the combination group of vitamin E 50 mg/kgbw and cisplatin compared to the cisplatin group. Conclusion: Vitamin E 200 mg/kgbw provides a protective effect against decreased spermatogonia, sertoli and leydig cells due to cisplatin 5 mg/kgbw exposure which its protectivity depends on the given dose.